Towards a legal regime of benefits sharing for space mining: With some experience from the Area. (June 2022) - Xu, Fengna; Su, Jinyuan
Abstract: As space resources have stimulated significant interest among governmental and private entities in recent years and the potential for benefits from Space Mining (SM) seems more tangible, determining how to share them requires clear international governance. Current space law does not specifically address benefit-sharing, and substantial disagreement remains among States whose levels of economic and scientific development differ. A similar issue existed in the negotiation of benefits from other common areas, such as the deep seabed. This article addresses the regime for sharing the benefits from SM and the corresponding regime of the Area, namely the seabed and ocean floor and subsoil thereof, beyond the limits of national jurisdiction. In view of the current legal, political and commercial context, the article suggests that the regime for sharing the future benefits from SM should be voluntary and mutually acceptable based on a free-market approach while considering the interests of developing States. It also proposes a specific mode of such a regime based on three elements: (a) the form of the benefits, (b) the resource categories, and (c) the development stages. The study concludes that the present focus should be on collaborative development of technology to facilitate SM for the common benefit and interests of humankind. Highlights: The current space law does not directly regulate benefits sharing of Space Mining. A clear regime is essential for intra-generational and inter-generational equity. The benefits sharing regime of Deep Seabed Mining may be relevant and instructive. Based on a free-market approach, while considering interests of developing States. Three valuable elements are: benefits forms, resource categories, development stages.